1987
DOI: 10.1346/ccmn.1987.0350507
|View full text |Cite
|
Sign up to set email alerts
|

Intervalence Electron Transfer and Magnetic Exchange in Reduced Nontronite

Abstract: Abstract--The effects of chemical reduction of structural Fe 3 § in nontronite SWa-1 (ferruginous smectite) on intervalence electron transfer (IT) and magnetic exchange were investigated. Visible absorption spectra in the region 800-400 nm of a chemical reduction series of the SWa-1 nontronite revealed an IT band near 730 nm (13,700 cm-'). Both the intensity and position of this band were affected by the extent of Fe reduction. The intensity increased until the Fe 2+ content approached 40% of the total Fe, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
47
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 16 publications
(14 reference statements)
9
47
1
Order By: Relevance
“…The deep bluegreen color, which arises from a near maximum in the Fe(II)-Fe(III) intervalence electron transfer transitions (Lear and Stucki, 1987;Komadel et al, 1990), clearly indicates that the reduced sample maintained a significant reduced state (~50%) during this stage of sample preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The deep bluegreen color, which arises from a near maximum in the Fe(II)-Fe(III) intervalence electron transfer transitions (Lear and Stucki, 1987;Komadel et al, 1990), clearly indicates that the reduced sample maintained a significant reduced state (~50%) during this stage of sample preparation.…”
Section: Methodsmentioning
confidence: 99%
“…This method is based on the intervalence electron transfer (IT) transition, which occurs between Fe(II) and Fe(III) in adjacent octahedral sites (Lear and Stucki, 1987). Twenty-five mg of sample was suspended in 2.5 ml of citrate-bicarbonate (CB) buffer solution and diluted with 37.5 ml of H20 in an inert-atmosphere reaction vessel (Stucki et al, 1984a).…”
Section: Methodsmentioning
confidence: 99%
“…The conductivity of electrons from the layer edge through the octahedral sheet would depend heavily on the presence of the transition metal. But Lear and Stucki (1987), based on measurements of magnetic exchange interactions and of intervalence electron transfer, concluded that structural Fe is reduced nearly randomly within the octahedral sheet. Reduction only from layer edges would likely create a reducing front Lear and Stucki (1987) clearly reject this possibility in ferruginous smectite.…”
Section: Resultsmentioning
confidence: 99%